2020
DOI: 10.1007/s00210-020-01947-6
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor contributes to lung vascular hyperpermeability in sepsis-associated acute lung injury

Abstract: Vascular endothelial growth factor (VEGF) is a prime regulator of vascular permeability. Acute lung injury (ALI) is characterized by high-permeability pulmonary edema in addition to refractory hypoxemia and diffuse pulmonary infiltrates. In this study, we examined whether VEGF can be implicated as a pulmonary vascular permeability factor in sepsis-associated ALI. We found that a great increase in lung vascular leak occurred in mice instilled intranasally with lipopolysaccharide (LPS), as assessed by IgM levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Therefore, we tested the status of VEGF and its effect on miR-1 in the injured endothelium. Consistent with previous reports ( 17 , 18 ), treatment with TNF-α or LPS increased VEGF expression in HPMECs ( Figure 3A and Supplemental Figure 1 ; supplemental material available online with this article; https://doi.org/10.1172/jci.insight.164816DS1 ). More importantly, the blockade of VEGF receptor 2 (VEGFR2), the main receptor for VEGF in ECs, completely abrogated miR-1 downregulation, showing the central role of VEGF signaling in miR-1 regulation ( Figure 3B ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, we tested the status of VEGF and its effect on miR-1 in the injured endothelium. Consistent with previous reports ( 17 , 18 ), treatment with TNF-α or LPS increased VEGF expression in HPMECs ( Figure 3A and Supplemental Figure 1 ; supplemental material available online with this article; https://doi.org/10.1172/jci.insight.164816DS1 ). More importantly, the blockade of VEGF receptor 2 (VEGFR2), the main receptor for VEGF in ECs, completely abrogated miR-1 downregulation, showing the central role of VEGF signaling in miR-1 regulation ( Figure 3B ).…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, inhibition of VEGF expression and signaling ameliorates the extent of injury in several models ( 46 , 56 58 ). A recent mechanistic study separating the endothelial and nonendothelial fractions of the injured lung concluded that during ALI, VEGF expression in ECs increases, while its expression in non-ECs and the whole lung decreases ( 17 ). The known stimulatory effect of LPS on endothelial VEGF is in line with this observation ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies suggest that VEGF may have a pathological role in ALI/ARDS in the short-term by contributing to increased permeability of the capillary membrane leading to noncardiogenic pulmonary edema 32 . However, other studies have found that VEGF may function through autocrine signaling as a pneumotrophic factor in the lung, facilitating recovery from lung injury in the long-term 11,[33][34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…VEGF has been evaluated in animal ALI models but the data regarding its role as a therapeutic agent have been conflicting ( Medford and Millar, 2006 ). In the short-term, VEGF may have pathologic effects by increasing alveolar-capillary membrane permeability within the EC niche and contributing to exudate formation ( Tomita et al, 2020 ). For example, SU5416, a potent and selective VEGFR2 inhibitor, ameliorated epithelial cell injury and histopathological changes in a murine ALI model following lipopolysaccharide (LPS) administration ( Huang et al, 2019 ).…”
Section: Translational Applicationsmentioning
confidence: 99%